Implementasi Program Parkir Elektronik (E-Parkir) di Kota Surakarta - Aulia Billqis; Retno Suryawati (Jurnal Mahasiswa Wacana Publik, 2022)
This study aims to describe the implementation of the electronic parking program in Surakarta City and also the factors that influence the program implementation process. This research method is descriptive qualitative with data collection techniques through interviews, documentation, and observation. The sampling technique was purposive sampling and the validity of the data was through technical and source triangulation. Data analysis techniques were carried out by data reduction, data presentation, and drawing conclusions. The results of the implementation show that the E-Parking program in Surakarta City is divided into four stages, namely the Planning Stage, Empowerment Stage, Implementation Stage, Monitoring and Evaluation Stage. From the results of this study, it can be concluded that the implementation of the E-Parking program has not fully met the aspects of compliance with the rules. As in the empowerment stage, when the socialization of e-parking to the community was not optimal, at the implementation stage there were still parking attendants who did not use tools. The obstacles found in the implementation are communication with the community and human resources, namely the quality and awareness of parking attendants is still lacking because some parking attendants do not use e-parking tools to collect parking fees. While the supporting factors for the implementation of e-parking are budgetary resources, disposition, and also the bureaucratic structure.